Kebersihan Lingkungan Kampus Pada Masalah Puntung Rokok di Universitas X - Himawan, Fayza Al Fairuz; Prasetyawan, Firnanda Putri; Levia, Nazwa Alva; Kinanti, Safira Putri; Puspita, Vani (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The environmental cleanliness problem on campus is caused by students' lack of awareness of the importance of maintaining a clean environment, especially regarding the disposal of cigarette butts. The objective of this study was to determine the campus environmental cleanliness regarding cigarette butt issues at University X. The research method employed direct observation supported by documentation. The subjects of this study consisted of 6 students from University X. The research findings revealed that there were instances of littering, specifically cigarette butts, in the campus area, and students were observed discarding cigarette butts into the fountain, which is considered to pollute water sources and damage the aesthetic appeal of the campus environment.